ANALISIS KEAKTIFAN SISWA DALAM KEGIATAN DISKUSI KELOMPOK PADA PEMBELAJARAN IPAS MATERI KEBERAGAMAN BUDAYA DI KELAS IV SEKOLAH DASAR - Nurshofa, Salwa; Herlina, Lina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low student engagement in the learning process remains a challenge in creating interactive and meaningful learning in elementary schools. This study aims to analyze student engagement in group discussions in science lessons on cultural diversity and identify factors influencing this engagement. The research method used was a qualitative approach with a case study, conducted at Sawahlega Elementary School. The subjects included fourth-grade students and their fourth-grade teacher as the primary informant. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The results showed that group discussions can increase student engagement, as indicated by student involvement in expressing opinions, asking questions, answering questions, and collaborating in groups. The use of visual media in discussions also increased student enthusiasm and understanding of cultural diversity. However, several obstacles to implementation exist, such as the persistence of student self-confidence, differences in ability between students, and limited learning time. This research is expected to contribute to teachers' development of more active, interactive, and enjoyable learning strategies to increase student engagement in elementary schools.